2021
DOI: 10.1111/jfir.12263
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity risk and the beta premium

Abstract: As opposed to the “low beta low risk” convention, we show that low beta stocks are illiquid and exposed to high liquidity risk. After adjusting for liquidity risk, low beta stocks no longer outperform high beta stocks. Although investors who “bet against beta” earn a significant beta premium under the Fama–French three‐ or five‐factor models, this strategy fails to generate any significant returns when liquidity risk is accounted for. Our work helps understand the beta premium from a new liquidity‐risk perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Racicot et al (2019) finds that illiquidity factor is important in the asset pricing model in the dynamic context. This is supported by Gong et al (2021), which finds that the liquidity factor could improve the performance of the Fama and French three-factor and five-factor models. Conversely, Safiuallah and Shamsudin (2021) finds that the inclusion of liquidity and interest rate factors does not improve the pricing ability of the model.…”
Section: Research Themes and Discussionmentioning
confidence: 71%
“…Racicot et al (2019) finds that illiquidity factor is important in the asset pricing model in the dynamic context. This is supported by Gong et al (2021), which finds that the liquidity factor could improve the performance of the Fama and French three-factor and five-factor models. Conversely, Safiuallah and Shamsudin (2021) finds that the inclusion of liquidity and interest rate factors does not improve the pricing ability of the model.…”
Section: Research Themes and Discussionmentioning
confidence: 71%
“…Therefore, when a firm proposes to make a major cross-industry M&A, investors and analysts in the capital market are prone to be optimistic (Wang et al , 2010), which is reflected in the fact that the market return rate is higher than that of intraindustry M&A. The research of Yang et al (2019) also supports the above view. They found that there is a premium of 8.42% in diversified M&A of listed firms in China.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 92%
“…Ross et al (1995) believes that financial risk is usually accompanied by the rapid development and expansion of enterprises because there must be some excessive debt-raising investment behaviors in this process. The impact of relevant national laws and regulations has brought about unstable student sources, annual differences in government funding, and lack of financial management supervision internal factor Xu, 2017 Property rights agency is not clear enough, extracorporeal circulation of income budget, project bidding for personal gain, vicious cycle of repaying old loans with new ones, and evaluation by the risk control department has not been implemented Huang, 2006 The salary system lacks incentives, and it is difficult for the school-run industry to achieve positive growth Wu, 2012 Infrastructure that exceeds the capacity of colleges and universities, rigid personnel system Liu & Liu, 2010 It is related to the inaccurate positioning of the school, blind comparison, cost accounting, and control system that need to be improved Huang, 2016 Financing by means of debt, resulting in debt risk Fu, 2011 Cash flow risk Gong, 2006 Lack of risk awareness and credit awareness, poor openness and transparency of financial information Zhang, 2018 School infrastructure investment, excessive investment, resulting in investment risk Li, 2015 Related to poor financial management and debt management Dong, 2015 Debt risk, investment risk, liquidity risk and institutional risk Wang, 2012 Universities debt continues to expand Cao, 2011 Imperfect internal control, imperfect management system, wrong investment decision-making, low level of capital management, indifferent risk awareness and low quality of personnel Ling & Ni, 2013 Unreasonable debt structure and huge interest…”
Section: Literature Reviewmentioning
confidence: 99%